Screening-level assessment of radon, thoron, and gamma radiation exposure in a TENORM-impacted tin mining area, Indonesia - Hikmat, Moh Cecep Cepi; Soesilo, Tri Edhi Budhi; Iskandar, Dadong; Soelarno, Soemarno Witoro; Yusuf, Muhammad; Syaeful, Heri (Brawijaya University, 2026)
Tin mining activities are frequently associated with Technologically Enhanced Naturally Occurring Radioactive Materials (TENORM), potentially increasing environmental radiation exposure. This study elucidated radon (²²²Rn), thoron (²²?Rn), and external gamma radiation in an artisanal tin-mining area in East Belitung Regency, Indonesia. Short-term measurements of radon and thoron were conducted at residential locations, while external gamma dose rates were measured at a tin-processing facility. Annual effective doses and excess lifetime cancer risks were estimated using internationally recommended parameters. Measured concentrations reflected uranium- and thorium-bearing minerals associated with granitic geology and surface disturbance typical of tin-mining regions. External gamma dose rates near ore concentrates and tailings exceeded local background levels, indicating technologically enhanced radiation fields from mineral processing. Although estimated annual effective doses remained below the recommended public limit of 1 mSv y?¹, external gamma radiation was the dominant contributor to total dose, with radon and thoron inhalation representing a secondary but significant pathway. This integrated evaluation emphasizes including thoron in radiation assessments of tin-mining areas, as radon-only assessments may underestimate inhalation exposure in thorium-rich environments. The findings provide baseline data for radiation protection strategies in artisanal mining communities and highlight the need for comprehensive TENORM monitoring in similar settings.